Aesthetic Appeal and Beyond: Examining the Influence of Restaurant Interior Design on Bangladeshi Consumers’ Satisfaction and Revisit Intention - Md. Tariqul Islam; Biswabhusan Pradhan; Uma Pandey; Siti Rahayu Hussin; Foong Yee Wong (ASEAN Journal on Hospitality and Tourism, 2023)
The primary motivation of the restaurant business is to serve consumers food and beverages and trigger them to make a repurchase. Moreover, it is a highly competitive business. The restaurant authorities employ several strategies to attract consumers to compete in the highly competitive industry and one of the leading practices in the restaurant industry is attracting guests with innovative and fascinating interior design. The purpose of conducting this study is to quantify the role of restaurants’ interior design on consumers’ revisit intention. Consumer satisfaction served as a mediator between restaurants' interior design and consumer revisit intention. An online survey was conducted on 393 Bangladeshi consumers to collect the data. The present study found a positive association among consumer satisfaction, restaurant interior design, and consumer revisit intention. This study contributes several theoretical and practical contributions for the academicians and the stakeholders of the restaurant industry.